A study of criteria for air cargo terminal classification model. Issue 4 (22nd August 2019) - Rodbundith, Treephis; Suthiwartnarueput, Kamonchanok; Pornchaiwiseskul, Pongsa
For global air cargo movement from airport to airport, the air cargo terminal is a key success factor of airlines and air cargo transport. This study is aimed to explore important criteria at air cargo terminals on the new integration of relevant and reviewed variables from academic researches and International Air Transport Association's regulated standards. To examine variables, the investigation of criteria significance is based on opinion and endorsed by 57 air cargo terminal operators covering 474 terminals around the world. Thereafter, the methodology is to evaluate the endorsed criteria and employs principal component analysis for criteria reduction onto correlation and similarity conditions by factor loading scores above 0.6. The remaining criteria are finally re-validated by aviation experts executed into nine main criteria with 44 sub-criteria. Moreover, the finding of air cargo terminal classification model is tested to cluster air cargo terminals in Thailand's major airports with the results of three classifications. Also, guidelines with factor loading scores from significant criteria are developed for air cargo industry for business investment and decision making purposes.